Quando os registros falam: um olhar sobre a violência sexual intrafamiliar contra crianças e adolescentes do Juizado da Infância e Juventude Cível de Manaus/AM - Pinheiro, Breno Pinto (Brasil, 2024)
The present research had the general objective of identifying the types of intrafamilial sexual violence against children and adolescents and their social context in the period between the months of January and March 2022 in the city of Manaus-AM and the specific objectives are: 1) map the processes that deal with intra-family sexual violence; 2) characterize the types of violence and; 3) identify the social context in which it occurred. The research is exploratory, documental and bibliographical and has expanded on the qualitative approach without, however, disregarding the quantitative approach which, according to Minayo, Deslandes, Neto and Gomes (2002), complement each other and support the analysis. The apprehension of the research object consisted of the analysis of testimonies contained in the matters of judicial proceedings that are being processed in the classes of Request for a Protection Measure, Execution of a Protection Measure, Providence, Custody and Loss or Suspension of Family Power of the Court for Children and Youth Civil of the Court of Justice of the State of Amazonas. The screened data consider that in the time period of the research, 58 cases were identified whose matter was the violation of children and adolescents' rights, of which 26 referred to intra-family sexual violence. The data showed that 79% of the cases of sexual violence were female victims and 21% were male victims, with a prevalence of rape of a vulnerable person, representing 41% of the total. Most of the crimes occurred in the victim's home environment and the perpetrators were predominantly concentrated on the father figure: stepfathers with 35% of the total number of perpetrators of the crime, followed by the parents, with 23%, thus configuring intrafamilial sexual violence. The study seeks to contribute to deepen the already existing bibliographical and documental production on the subject and to assume the social cult when it proposes to shed light on this perverse expression of the social issue, heating up the debate around the institution's problem of interest, the locus of the research, academics, Social Work professionals and related areas of knowledge.